Le passé indien et l’avenir de la nation au Mexique :Retour sur l’anthropologie critique de Guillermo Bonfil Batalla - Miriam Hernández Reyna (Les Cahiers ALHIM)
The Indian past in Mexico has been the subject of several interpretations, linked to different future projects for the nation. At the end of the 20th century, a trend known as “critical anthropology” emerged from which a re-reading of this past was initiated. The anthropologist Guillermo Bonfil Batalla belonged to this generation marked by a Marxist revival and a critique of the notions of civilization and progress. In this article we restitute several elements of the intellectual history of Bonfil Batalla. First, we situate his thinking in the context of an international anthropology that denounced the conditions of the lives of indigenous peoples in independent nation-states, and then we examine how the anthropologist's thinking feeds on these elements and contributed to create the critical trend in anthropology and its application in Mexico. We will see how the anthropology of Bonfil Batalla, critical and politically involved with the indigenous question in Mexico, was the culmination of a renewal in the perception of the Indian past, understood not as a burden to build modernity, but as a source of hope and liberation for a nation, previously contented to be the distorted copy of an imaginary West.